2020
DOI: 10.1002/vzj2.20059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microplastics and earthworm burrows on soil macropore water flow within a laboratory soil column setup

Abstract: Several earlier studies reported that microplastics (MP) accumulated on soil surfaces could be transported into the subsoil and ingested by soil biota, such as earthworms. The present study explores how networks of earthworm burrows and MP (low-density polyethylene, LDPE) in subsoil affect the soil hydraulic properties and saturated water flow. A repacked and saturated sandy soil column experiment was conducted in an environment-controlled laboratory with earthworms (anecic, Lumbricus terrestris) inoculated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Instead of artificially incorporating microplastics into soil, Yu, van der Ploeg, Ma, Ritsema, and Geissen (2020) placed polyethylene pieces (∼4 g) on the surface of a sandy soil (7 kg air-dried soil in a 11.6-cm × 50-cm column) in the absence and presence of earthworms, and they found that although polyethylene pieces were transported by earthworms into soil, polyethylene did not affect the saturated hydraulic conductivity of the soil. These results indicate that the effect of microand nanoplastics on soil hydraulic properties depends on plastic characteristics as well as soil texture.…”
Section: Effects Of Micro-and Nanoplastics On Soil Hydraulic Propertiesmentioning
confidence: 99%
“…Instead of artificially incorporating microplastics into soil, Yu, van der Ploeg, Ma, Ritsema, and Geissen (2020) placed polyethylene pieces (∼4 g) on the surface of a sandy soil (7 kg air-dried soil in a 11.6-cm × 50-cm column) in the absence and presence of earthworms, and they found that although polyethylene pieces were transported by earthworms into soil, polyethylene did not affect the saturated hydraulic conductivity of the soil. These results indicate that the effect of microand nanoplastics on soil hydraulic properties depends on plastic characteristics as well as soil texture.…”
Section: Effects Of Micro-and Nanoplastics On Soil Hydraulic Propertiesmentioning
confidence: 99%
“…8 ). Water flows through soil macropores; in fact, we regard the phenomena as soil macropore flow (Yu et al 2020 ). In general, soil macropore flow is mainly influenced by the size and number of soil macropores, the hydrophobic organic coatings of soil macropores boundaries, the amount of surface water supply, and the temperature of infiltrating water (Watanabe and Kugisaki 2017 ; Beven 2018 ).…”
Section: Hydrological Connectivity At Multiscales and Its Effects On Ecohydrologymentioning
confidence: 99%
“…Agricultural soil is a research focus, where the technology of polyethylene film-mulching is used extensively to alter crop microclimates and reduce water evaporation (Liu et al, 2019;Wang et al, 2020), causing mass production of MP in agricultural farmland (Wanner, 2021). Plastics are fragmented into MPs during the tillage, and some remain on the surface of the soil while others are buried under the soil (Ding et al, 2019); the MPs further travel and redistribute in soils with water flow (Song et al, 2017;Yu et al, 2020). Therefore, the impact of MP accumulation in various soil mediums should be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the impact of MP accumulation in various soil mediums should be assessed. Recently, MP production and migratory and accumulative behaviors have attracted significant interest (Cesa et al, 2017;Hurley & Nizzetto, 2018;Maaß et al, 2017;Yu et al, 2020). Microplastic pollution in agricultural soils has also been of increasing concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation